ANALISIS FAKTOR MINAT MASYARAKAT SEMARANG DALAM PENGGUNAAN GOPAY SEBAGAI DIGITAL PAYMENT TECHNOLOGY ACCEPTANCE MODEL - Sinta Nugraheni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
This study aims to analyze the interest of the Semarang city’s community in using GOPAY as a digital payment based on the Technology Acceptance Model (TAM). The TAM approach was chosen because TAM is the most widely used model in predicting the acceptance of information technology and has proven to be a very useful theoretical model in helping to understand and explain user behavior in the implementation of using GOPAY as a digital payment. Nowadays, people who used to use cash payment (cash based) have now started to recognize and use non-cash payments (non-cash) in carrying out various payment transaction activities. One of the non-cash payment instruments that is currently developing is electronic money, one of which is GOPAY. The sample of this study was 100 people in the city of Semarang. The data analysis technique is multiple linear regression. The results of the research are Perceptions of Benefits, Perceptions of Ease, User Attitudes, and Perceptions of Security that have a positive effect on interest in using GOPAY as a digital payment.